HORIZONTE DE LA SEGURIDAD INFORMÁTICA EN LA ERA DE LA INDUSTRIA 4.0 - John Alexander Rico Franco (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2020)
Today’s humanity thanks to the third industrial revolution, has relied on technology as a mechanism of evolution towardsa new digital way of life, where today smart computing devices are becoming more common and therefore it started topermeate more easily on different areas of our society, and together with the help of an amazing telecommunications medium as massive and dynamic just as the contemporary Internet, has allowed to view a new industrialized model forthe manufacture of industrialized products in an automatic and autonomous way; this concept is called the fourthindustrial revolution or industry 4.0, where the interconnectivity based on the Internet of things and the intelligent androbotic technological elements, deploy a new and refreshing industrial model. This new industrial revolution as well as any technological revolutionary trend with high impact for humanity, always areaccompanied by an urgent need to be evaluated and safeguarded with the parameters of today’s computer security, whichmay be limited or insufficient for the ideology of the industry 4.0, this is because the existing IT security activities areinsufficient for such massive, distributed, insecure and critical environment as the proposed by the next generationproduction plants and therefore at the same time the companies must evolve to adopt the native production processes ofthe fourth industrial revolution, the computer security specialists must also develop their concepts, technologies andactivities, to design and manage highly secure production environments aligned with the requirements and vulnerabilitiesof this new industrial generation.The ultimate purpose of this document is to present how current IT security should begin to see the industry 4.0 as its newfield of action, because without a robust technological protection model any deployment of new generation industrialfunctions it would be completely catastrophic for the company that wishes to evolve thanks to the adoption of this newbusiness archetype. This article is segmented by the presentation of a context by the principles of the fourth industrialrevolution, where some key foundations of this technological trend are exhibited, and then go on to exhibit a safetyanalysis on the different segments that make up a factory of new generation, to then identify some of the most interestingtrends of attack that modern cybercriminals are beginning to deploy to violate complex industrial systems, and finallypresent some safety recommendations based on the study of the native vulnerabilities of a generic factory 4.0 along withthe newest styles of digital aggression focused on this amazing but defenseless new generation industrial guideline.